The prevalence of early subclinical somatic neuropathy in children and adolescents with Type 1 diabetes mellitus and its association with the persistence of autoantibodies to glutamic acid decarboxylase (GAD) and islet antigen-2 (IA-2). (July 2016) - Louraki, Maria; Katsalouli, Marina; Kanaka-Gantenbein, Christina; Kafassi, Nikolitsa; Critselis, Eleni; Kallinikou, Dimitra; Tsentidis, Charalampos; Karavanaki, Kyriaki
Highlights: Among examined nerves, the sensory peroneal nerve had the highest abnormality rates. The persistence of GADA and IA-2A was associated to slower peronial action potentials. Autoantibodies may be involved in axonal degeneration in early diabetic neuropathy. Abstract: Aim: To evaluate the prevalence of early somatic neuropathy in children and adolescents with Type 1 diabetes mellitus (Type 1 DM) and its association with the presence of glutamic acid decarboxylase and islet antigen-2 autoantibodies (GADA and IA-2A). Methods: A cross-sectional study was conducted in a hospital-based cohort of pediatric Type 1 DM patients ( n = 85, mean(±SD) age: 13.5 ± 3.4 years, mean(±SD) disease duration 5.5 ± 3.4 years). Peripheral neuropathy was assessed with nerve conduction studies (NCS). GADA and IA-2A titers were measured with radioligand assays. Results: Among the study population, 34.1% had at least one abnormal electrophysiological parameter, although predominantly asymptomatic. The highest rates of abnormality were detected in sensory peroneal nerve (25.9%) followed by sural nerve (15.3%). Affected patients were not different in terms of age, diabetes duration or glycaemic control. Among the participants, 62.4% had positive GADA, 58.8% positive IA-2A and 42.4% double antibody positivity. Abnormal NCS correlated neither with GADA nor with IA-2A levels or positivity. However lower sensory nerve action potential in the peroneal nerve, indicative of early axonal dysfunction, was observed in patients with GADA or IA-2A positivity. Absence of both antibodies was associated with better action potentials in all the examined nerves of the lower limbs. Conclusions: Impaired indices of subclinical peripheral primarily sensory neuropathy were present among one third of Type 1 DM children and adolescents, with no impact of diabetes duration or glycaemic control. GADA and IA-2A seem to be involved in the development of axonal degeneration, in a pathway which remains to be identified.